Renewable bioresources : scope and modification for non-food applications. - Stevens, Christian, 1965-; Verhé, Roland, 1944- (Chichester : Wiley, 2004)
Renewable Bioresources: scope and modification for non-food applications is the first text to consider the broad concept of renewable materials from the socio-economic aspects through to the chemical production and technical aspects of treating different raw products. The text sets the context of the renewables debate with key opening chapters on green chemistry, and the current situation of US and EU policy regarding sustainability and industrial waste. The quantitative and technical scope and production of renewable resources is then discussed with material looking at integral valorisation, the primary production of raw materials, downstream processing, and the identification of renewable crop materials. The latter part of the book concludes with a discussion on the uses for renewable materials such as carbohydrates, woods, fibres, biopolymers, lipids and proteins in different industrial applications, including a key chapter on the high value-added industries.
Keywords: Biopolymeren; Chemische industrie; Milieuchemie